Implementasi Ujian Nasional Di Kota Medan (Studi Kasus Pada SMP Kota Medan) - N Heliwati (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to determine the implementation of national examinations in Medan City (Case study on Medan City Middle School). From this purpose we will see the perceptions, attitudes and behavior of principals, teachers, parents, and students on the implementation of national examinations in Medan city junior high schools. This research was carried out using a qualitative approach. Data collection in the study used the observation method of FGD (Focus Group Discussion) and document review. The subjects of this study were the Principals, Teachers, Parents and Students of Medan City Middle School who were taken through purposive sampling and snowball sampling techniques. Analysis of the findings of this study will be conducted according to the type of data collected. This data analysis process includes three stages, namely data reduction, data display and conclusion. After the data was analyzed, there were three research findings, namely: First, Principal Perception, Teachers, Parents and Students on the implementation of the national exam in SMP in Medan City showed varied data. Second, the attitude of principals, teachers, parents and students to national examinations. In responding to the implementation of the national exam, the Principal supports and approves the existence of a national examination. Third, the behavior of principals, parents, teachers and students on the implementation of the national exam. The behavior of school principals towards the implementation of the national exam by fully supporting the national exam and preparing various activities that will help students who will take the national exam, such as holding and increasing additional tutoring, especially the subjects to be tested.